Present: A Screenplay Exploring the Effects of the Absence of a Father to a Female Young-Adult - Tiara Katherine; Ribut Basuki (Institute of Research and Community Outreach - Petra Christian University, 2025)
A good dynamic of parental involvement is needed in the child’s psychological development. Especially the father's involvement in the daughter’s life which can have lasting effects on how the daughter feels about herself, future choices, preferences, and how she feels about herself. Using psychosocial theory, this creative thesis highlights the effects of disengaged or emotionally unavailable fathers to a female young-adult in her early childhood. An absent father will result in the child’s psychological well-being as they feel insecure and not confident, as well as seeking for older partners later in life who can fulfill their emotional void they experienced during childhood. Through this screenplay, it is shown that a father's involvement in the child’s life is crucial to shape who the child will become in the future.